WHY THE NEED FOR CONSUMER PROTECTION LEGISLATION? A LOOK AT SOME OF THE REASONS BEHIND THE PROMULGATION OF THE NATIONAL CREDIT ACT AND THE CONSUMER PROTECTION ACT - Tanya Woker (Obiter, 2021)
Two statutes focusing on consumer protection have been introduced recently: the Consumer Protection Act due to come into effect in October 2010 and the National Credit Act. There are many who criticize this legislation, arguing that this will overburden the economy and will lead to significant costs for business. In this article I examine some of the reasons why the Department of Trade and Industry deemed it necessary to introduce consumer protection legislation. I conclude by arguing that despite the increased costs for business, the legislation is necessary in order to prevent the exploitation of consumers by business that presently exists in South Africa. I do not, however, seek to answer the question whether this legislation will achieve its lofty aims. This, only time will tell. However, many acknowledge that the introduction of the National Credit Act shielded South Africa from some of the worst excesses of the global recession of 2008/2009. It is hoped that the Consumer Protection Act will likewise change the way many in South Africa do business.